2014
DOI: 10.3938/jkps.65.696
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and thermoelectric properties of iodine-doped Bi2Te3-Bi2Se3 solid solutions

Abstract: Bismuth chalcogenides, such as p-type (Bi,Sb)2Te3 and n-type Bi2(Te,Se)3, are known to have excellent thermoelectric properties at temperatures near room temperature. Since Bi2Te3, Sb2Te3 and Bi2Se3 have the same class of crystal symmetry, they can form homogeneous solid solutions. The thermoelectric figure of merit can be improved by increasing the power factor through doping to optimize the carrier concentration and/or by reducing the thermal conductivity through the formation of solid solutions for phonon s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…[ 3 ] The p-type bismuth tellurides show high zT values in the hot-deformed Bi 0.3 Sb 1.7 Te 3 (1.3 at 380 K) [ 4 ], Te-excess Bi 0.4 Sb 1.6 Te 3 (1.41 at 147 K) [ 5 ], melt-spun BiSbTe alloys (1.24 at 350 K [ 6 ] and 1.56 at 300 K [ 7 ]). The n-type bismuth tellurides also show relatively high zT values such as hot-deformed Bi 2 Te 2.3 Se 0.7 (1.2 at 445 K) [ 4 ], Cu-doped polycrystalline Bi 2 Te 2.7 Se 0.3 (1.10 at 373 K) [ 8 ], I-doped polycrystalline Bi 2 Te 2.7 Se 0.3 (1.13 at 423 K) [ 9 ], CuI-doped Bi 2 Te 2.7 Se 0.3 with hot-deformation (1.07 at 423 K) [ 10 ], textured Bi 2 Te 2.7 Se 0.3 nano crystal (1.31 at 438 K) [ 11 ], Se-deficiency polycrystalline Bi 2 Te 2.3 Se 0.69 (1.2 at 450 K) [ 12 ] and hot-deformed Bi 1.95 Sb 0.05 Te 2.3 Se 0.7 ( zT = 1.3 at 450 K) [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 3 ] The p-type bismuth tellurides show high zT values in the hot-deformed Bi 0.3 Sb 1.7 Te 3 (1.3 at 380 K) [ 4 ], Te-excess Bi 0.4 Sb 1.6 Te 3 (1.41 at 147 K) [ 5 ], melt-spun BiSbTe alloys (1.24 at 350 K [ 6 ] and 1.56 at 300 K [ 7 ]). The n-type bismuth tellurides also show relatively high zT values such as hot-deformed Bi 2 Te 2.3 Se 0.7 (1.2 at 445 K) [ 4 ], Cu-doped polycrystalline Bi 2 Te 2.7 Se 0.3 (1.10 at 373 K) [ 8 ], I-doped polycrystalline Bi 2 Te 2.7 Se 0.3 (1.13 at 423 K) [ 9 ], CuI-doped Bi 2 Te 2.7 Se 0.3 with hot-deformation (1.07 at 423 K) [ 10 ], textured Bi 2 Te 2.7 Se 0.3 nano crystal (1.31 at 438 K) [ 11 ], Se-deficiency polycrystalline Bi 2 Te 2.3 Se 0.69 (1.2 at 450 K) [ 12 ] and hot-deformed Bi 1.95 Sb 0.05 Te 2.3 Se 0.7 ( zT = 1.3 at 450 K) [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Even though the thermoelectric performance of n-type bismuth tellurides has been progressing significantly, the zT values of the n-type materials are not compatible with those of the p-type properties because the thermoelectric device’s performance is mainly determined by the average zT values of p-and n-type materials. [ 14 ] To reach high thermoelectric performance in n-type bismuth tellurides, there have been many studies such as the control of Se concentration Bi 2 Te 3−x Se x [ 4 , 11 , 15 , 16 ], Cu-doping [ 8 , 17 ], I-doping [ 9 , 17 ] Ga-doping [ 18 ], CuI-doping [ 10 , 19 , 20 ], hot-press and hot-deformation processes [ 8 , 13 , 21 , 22 , 23 , 24 ], etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dataset consists of Seebeck coefficient a, electrical resistivity r, and thermal conductivity k at measured temperature T. For the numerical computation of efficiency, we use the available temperature ranges of the given material: the T c is defined as the maximum of the lowest measured temperautre and T h is defined as the minimum of the highest measured temperature for given materials. Heremans et al (2008); Hsu et al (2004);Hu et al (2014Hu et al ( , 2016; Kim et al (2015c); Lin et al (2016); Liu et al (2011Liu et al ( , 2012b; Pan and Li (2016); Pei et al (2011g, 2011c; Poudel et al (2008); Rhyee et al (2009); Wang et al (2014a); Zhao et al (2012aZhao et al ( , 2012bZhao et al ( , 2014Zhao et al ( , 2015; Cui et al (2007Cui et al ( , 2008; Eum et al (2015); Fan et al (2010); Han et al (2013); Hsu et al, 2014;Zheng et al (2014);Hu et al (2015); Hwang et al (2013); Ko et al (2013); Zhang et al (2015b); Zhao et al (2005); Lee et al (2010Lee et al ( , 2013cLee et al ( , 2013a; Yan et al (2010); Lee et al (2013bLee et al ( , 2014cLee et al ( , 2014bLee et al ( , 2014aLee et al ( , 2014d (2011a, 2011e, 2011f, 2011d, 2012a, 2012b, 2014);…”
Section: Published Thermoelectric Property Datamentioning
confidence: 99%
“…Lee et al [13] reported that the increase in the carrier concentration induced by I doping led to an increase in the electrical conductivity. The ZT value was improved by I doping due to the increased PF, demonstrating a maximum of ZT ¼ 1.13 at 423 K for Bi 2 Te 2.7 Se 0.3 :I 0.0075 .…”
Section: Introductionmentioning
confidence: 99%